Behavioral response to imipramine under chronic mild stress corresponds with increase of mRNA encoding somatostatin receptors sst2 and sst4 expression in medial habenular nucleus. (December 2018) - Faron-Górecka, Agata; Kuśmider, Maciej; Solich, Joanna; Kolasa, Magdalena; Gruca, Piotr; Pabian, Paulina; Szlachta, Marta; Dziedzicka-Wasylewska, Marta
Graphical abstract: Highlights: Using in situ hybridization, the expression of mRNA encoding sst2R and sst4R was observed in the rat hippocampus and medial nucleus of habenula (MHb). Rats subjected to CMS and treated with imipramine (IMI), reacted to the drug treatment, with reduced anhedonia. Alterations of mRNA level encoding sst2R and sst4R located in the MHb corresponds with the behavioral response of animals after CMS.